2018
DOI: 10.1111/jcpe.12993
|View full text |Cite
|
Sign up to set email alerts
|

The effect of periodontal therapy on oxidative stress biomarkers: A systematic review

Abstract: Periodontal therapy reduces the levels of OxS biomarkers, even to values similar to those found in periodontally healthy individuals. Additional RCTs are warranted, as the information is mainly based on nonrandomized studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 65 publications
3
13
0
1
Order By: Relevance
“…The results of our meta‐analysis revealed that TOS in the saliva and GCF was significantly higher in CP patients compared to PH individuals, which was consistent with previous findings (Akalin et al., ; Wei et al., ). Moreover, a latest systematic review revealed that periodontal therapy was effective in reducing TOS in GCF, saliva, and serum in CP patients (da Silva et al., ), which further confirmed our recent results. However, no significant difference in the salivary TOS between CP patients and PH controls was reported (Zhang et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…The results of our meta‐analysis revealed that TOS in the saliva and GCF was significantly higher in CP patients compared to PH individuals, which was consistent with previous findings (Akalin et al., ; Wei et al., ). Moreover, a latest systematic review revealed that periodontal therapy was effective in reducing TOS in GCF, saliva, and serum in CP patients (da Silva et al., ), which further confirmed our recent results. However, no significant difference in the salivary TOS between CP patients and PH controls was reported (Zhang et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…The relationship between oxidative stress and periodontal disease is quite strong and can be a two-way path. On one hand, the presence of periodontal inflammation increases the number of oxidative stress markers, and on the other hand, it tends to potentiate aspects of periodontal destruction [35].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are numerous substances produced during periodontal tissue remodeling as reported in basic research in periodontal diseases; these substances best reflect the condition of the periodontal tissue and are so-called proximal fluids near lesion areas, also referred to as gingival crevicular fluid (GCF) that are widely used as samples [ 76 , 77 , 78 ]. The gingival sulcus is the furrow between the teeth and the gums, and the gingival sulcus exists around the teeth in a V-shaped space.…”
Section: Proteome Analysis Of Molecular Events In Oral Pathogenesimentioning
confidence: 99%